2011
DOI: 10.1371/journal.pone.0018774
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity Elicited by Positive and Negative Feedback in Preschool-Aged Children

Abstract: To investigate the processing of positive vs. negative feedback in children aged 4–5 years, we devised a prize-guessing game that is analogous to gambling tasks used to measure feedback-related brain responses in adult studies. Unlike adult studies, the feedback-related negativity (FRN) elicited by positive feedback was as large as that elicited by negative feedback, suggesting that the neural system underlying the FRN may not process feedback valence in early childhood. In addition, positive feedback, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
5
20
1
Order By: Relevance
“…A baseline correction was performed with baselines specified as follows: −200 to −100ms prior to response onset for ERN and CRN, Pe and Pc segments, −100 to 0ms for FRN (positive and negative feedback) segments, and −100ms to 0ms prior to stimulus onset for Go and No-go N2 segments. Based on initial visual inspection of the grand averaged ERPs, and in accordance with previously published reports (Espinet, Anderson, & Zelazo, 2012; Grammer et al, 2014; Mai et al, 2011), we defined ERP component windows of interest as the following: The ERN was defined as the average amplitude between −25 and 50ms aligned with response onset. The Pe was defined as the average amplitude between 200 and 500ms after the response onset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A baseline correction was performed with baselines specified as follows: −200 to −100ms prior to response onset for ERN and CRN, Pe and Pc segments, −100 to 0ms for FRN (positive and negative feedback) segments, and −100ms to 0ms prior to stimulus onset for Go and No-go N2 segments. Based on initial visual inspection of the grand averaged ERPs, and in accordance with previously published reports (Espinet, Anderson, & Zelazo, 2012; Grammer et al, 2014; Mai et al, 2011), we defined ERP component windows of interest as the following: The ERN was defined as the average amplitude between −25 and 50ms aligned with response onset. The Pe was defined as the average amplitude between 200 and 500ms after the response onset.…”
Section: Methodsmentioning
confidence: 99%
“…Mai and colleagues (2011) used a prize-guessing task to examine the FRN in 4- and 5-year-old children, and found no difference in amplitude between positive and negative outcomes. Roos, Pears, Bruce, Kim, and Fisher (2014) examined the FRN in a performance-based flanker task in a sample of maltreated preschool children, and found larger FRN amplitudes for negative outcomes, but only in children who were also high in impulsivity.…”
Section: The Ern Pe Frn and No-go N2 Componentsmentioning
confidence: 99%
“…Although their results on ERP latency were coherent with our findings, Mai and colleagues (2011) were unable to find indications of a distinction with respect to outcome correctness. This discrepancy might be because of the different feedback-reward procedures used in their study (see Mai et al, 2011). Mai and colleagues (2011) used a game in which childrenʼs actions were always rewarded with a prize, with the outcomes varying between "nicest" and "least nice" prizes, based on individual rank ordering.…”
Section: Characteristics Of the Feedback-related Brain Potentials In mentioning
confidence: 99%
“…Despite the fact that, to our knowledge, the MFN has not yet been detected in children, other related components such as the N2 (Lukie, Montazer-Hojat, & Holroyd, 2014), feedback-related negativity (FRN; Mai et al, 2011), and error-related negativity (ERN; Wiersema, Van Der Meere, & Roeyers, 2007) have already been reported in children. These components, also related to unexpected outcomes detection, are considered to have the same anatomical source of MFN, namely the ACC.…”
Section: Please Scroll Down For Articlementioning
confidence: 73%
“…Particularly with regard to the UG the MFN points to spontaneous processing of unfairness, indicating that children's perception and behavior are already driven by expectations of fair interactions. Previous studies had already investigated components related to MFN, such as N2 (Lukie et al, 2014), FRN (Mai et al, 2011), and ERN (Wiersema et al, 2007) in children as well. These studies have found similarities between adults and children with regard to the effects modulating these components, with an overall difference only in amplitude (Lukie et al, 2014).…”
Section: Mfn Response To Inequity In Childrenmentioning
confidence: 99%